Eye-related Emergency Department Visits with Ophthalmology Consultation in Taiwan: Visual Acuity as an Indicator of Ocular Emergency - Kang, Eugene Yu-Chuan (Sci Rep, 2020)
To investigate the epidemiology of eye-related emergency department (ED) visits and to determine if visual acuity (VA) could be an indicator for determining the timing for managing ocular emergencies, we have conducted the retrospective study which included patients visited the ED for eye-related reasons and had received ophthalmology consultations at a referral center in Taiwan in 2015. Among 46,514 consultations, 5,493 were ophthalmology consultations (11.8%). After exclusion, 5,422 were eligible for analysis. Among them, 1,165 (21.5%) had not likely emergent diagnoses, 4,048 (74.7%) had likely emergent diagnoses, and 209 patients (3.9%) could not be determined. The logMAR VA was 0.31 ± 0.48, 0.66 ± 0.78, and 1.00 ± 0.94 in groups with not likely emergent, likely emergent, and undetermined diagnoses, respectively. Among all eye-related ED visits, 10.3% of patients received ophthalmologic intervention or were admitted to the ophthalmology ward. A LogMAR VA score of 0.45 (decimal equivalent of 0.4) had the highest discrimination power for identifying whether a patient needed ophthalmology intervention or admission to ophthalmology ward (area under the curve: 0.802, sensitivity: 0.800, specificity: 0.672). In our study, we found VA could be an indicator for determining the priority and time of ocular emergencies requiring ophthalmic intervention in patients visiting the ED for eye-related reasons.